2017
DOI: 10.5539/gjhs.v9n7p161
|View full text |Cite
|
Sign up to set email alerts
|

Shielding Evaluation of Diagnostic X-Ray Rooms in Khartoum State

Abstract: The purpose of this study is to evaluate the shielding of some conventional x-ray rooms in Khartoum state. This study is based on the shielding calculations stated in the NCRP report number 49. This is the first time in Sudan to evaluate the shielding of diagnostic x-ray rooms based on this report.The total number of conventional x- ray rooms included in this study is 9 and the main parameters recorded during the evaluation are the KVp, mAs, and distance from the x-ray source to the measuring points. The dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
3
2
Order By: Relevance
“…Alameen et al 8 concluded that the majority of the tested x-ray rooms (approximately 89%) do not comply with the international recommendations as far as the shielding thickness is concerned, whereas our results stated that depending on the hospitals structures, 64.3% of the hospitals contain an x-ray in their theater, and only 40.5% of them are shielded.…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…Alameen et al 8 concluded that the majority of the tested x-ray rooms (approximately 89%) do not comply with the international recommendations as far as the shielding thickness is concerned, whereas our results stated that depending on the hospitals structures, 64.3% of the hospitals contain an x-ray in their theater, and only 40.5% of them are shielded.…”
Section: Resultscontrasting
confidence: 84%
“…The dosimeter is a tool that can measure the amount of absorbed dose of ionizing radiation that the radiologist had been exposed to. Individual external doses can be assessed by using individual monitoring devices 8 . None of these devices are used in all hospitals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Possible reasons for the similarity might be because of the involvement of experts during the construction of the x-ray room or overestimation of the shielding calculations. However, findings from this study are dissimilar to that of [11]. The possible reasons for the dissimilarities might be related to the shortage of qualified experts for room design or the absence of supervision and regulatory authority in the establishment of such an x-ray room.…”
Section: Discussioncontrasting
confidence: 83%
“…Although at first glance it might seem to be an easy and trivial job, shielding design for medical X-ray imaging facilities may be a difficult task since several variables and data must be taken into account, which means the calculation of barrier requirements include many uncertainties. It has been thoroughly and worldwide pointed out in the literature [4][5][6]. The design and shielding barriers in a diagnostic X-ray department generally follows the ALARA principle.…”
Section: Introductionmentioning
confidence: 99%